2021
DOI: 10.1111/1346-8138.15950
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a moisturizer for pruritus accompanied by xerosis in patients undergoing dialysis: A multicenter, open‐label, randomized verification study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Only a few mild skin inflammatory reactions were reported in the MPS cream groups, such as erythema, burning, and tingling at the application site. Many clinical trials also had the same results that no systematic AEs were related to the MPS cream (46,47). With regard to the incidence of skin inflammatory reactions, MPS cream was comparable to vaseline ointment and was superior to urea cream.…”
Section: Discussionmentioning
confidence: 74%
“…Only a few mild skin inflammatory reactions were reported in the MPS cream groups, such as erythema, burning, and tingling at the application site. Many clinical trials also had the same results that no systematic AEs were related to the MPS cream (46,47). With regard to the incidence of skin inflammatory reactions, MPS cream was comparable to vaseline ointment and was superior to urea cream.…”
Section: Discussionmentioning
confidence: 74%
“…Concerning dialysis, the baseline scores for dryness, pruritus, insomnia, and DLQI are close to the data in the literature. 11 , 12 Four previous studies demonstrated the efficacy of an emollient in xerosis and uremic pruritus, 7 , 8 , 31 , 32 but only one evaluated the skin-related quality of life. 32 Interestingly, uremic pruritus affected the quality of life of patients with end-stage renal disease, 11 , 12 but not xerosis (evaluated by the El Gammal index), corresponding more to a prognostic factor for worsening of the skin-related quality of life.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 12 Four previous studies demonstrated the efficacy of an emollient in xerosis and uremic pruritus, 7 , 8 , 31 , 32 but only one evaluated the skin-related quality of life. 32 Interestingly, uremic pruritus affected the quality of life of patients with end-stage renal disease, 11 , 12 but not xerosis (evaluated by the El Gammal index), corresponding more to a prognostic factor for worsening of the skin-related quality of life. 12 In the current study, similarly only a correlation between pruritus with DLQI was observed.…”
Section: Discussionmentioning
confidence: 99%
“…72 In studies that measure skin dryness/skin hydration as one of the outcomes, these various topical forms (gels, creams, emulsions, lotions, and solutions) can also reduce skin dryness or improve skin hydration. 68,70,75,76,78,80,84,85,87 Topical drug preparations consist of active ingredients (drugs) in a base (vehicle), and excipients (e.g., emulsifiers, antioxidants, and preservatives). 65,88 A good topical drug preparation contains a composition of basic ingredients that can improve the function of the epidermal barrier.…”
Section: Topical Treatmentmentioning
confidence: 99%
“…However, almost all active ingredients used as topical treatment in these studies were shown to significantly reduce pruritus intensity, except Tacrolimus ointment 0.1% 69 and Dead Sea (DS) minerals 72 . In studies that measure skin dryness/skin hydration as one of the outcomes, these various topical forms (gels, creams, emulsions, lotions, and solutions) can also reduce skin dryness or improve skin hydration 68,70,75,76,78,80,84,85,87 …”
Section: Treatmentmentioning
confidence: 99%